The Effect of Facebook and Word of Mouth Social Media Promotion on Purchase Decisions at Caf Rumi Cisarua, Bogor Regency - Lutfi, Muhammad (International Journal of Managemen Analytics (IJMA), 2024)
This research aims to understand and analyze the impact of Facebook and word of mouth social media promotions on purchasing decisions at Café Rumi Cisarua, Bogor Regency. This research is a type of descriptive verification research. The population in this study were consumers of the Rumi Cisarua Café, Bogor Regency. This research used a sample of 81 people using the Taro Yamane method. Data collection methods in this research are questionnaires, interviews and literature studies. This research uses multiple linear regression analysis. The research results show that Facebook social media promotion and word of mouth have a positive and significant effect simultaneously and partially on purchasing decisions.